The Use of Expert Testimony and Results of Search Operations in the Criminal Process in Keeping with Decisions of the European Court of Human Right - Irina E. Nikitina (Теория и практика судебной экспертизы, 2017)
The paper examines the problem of using expert testimony and the results of search operations in adversarial courts in keeping with decisions issued by the European Court of Human Rights. It includes a summary of Strasbourg Court rulings concerning search operations and the use of their outcomes. The author lists key requirements imposed by the Strasbourg Court on expert witnesses participating in judicial inquiries.